Traffic Adaptive Schedule-Based Mac Protocol For Wireless sensor Networks - Vahabi, Maryam (2008)
Wireless sensor networking is an emerging technology that has a wide range of potential applications inc1uding monitoring, medical systems, real-time, robotic exploration and etc. Energy is a critical resource in battery-powered sensor networks. Medium access control has an important role in minimizing energy consumption while it is responsible for successful data transferring in the network. Periodic data collection is the most comprehensive way of data gathering mechanism in wireless sensor network in which nodes report their samples in specific time interval s . It is possible to h ave some nodes with different update interval s in the network and therefore, finding a solution to accommodate nodes with different sampling intervals while maintaining the energy efficiency is the primary concern of this thesis.